Evaluation of ADL self-management module on quality of life among road traffic crash patients with lower extremities fractures in Taif City Hospitals, Saudi Arabia - Althomali, Majed Eidah (2019)
Background: Road traffic crashes have elicited concern from the community and the government in Saudi Arabia and worldwide. Moreover, Road traffic crashes can lead to injuries, disabilities and deaths. Injuries from Road traffic crashes are among the main causes of physical and functional disabilities. Therefore, the ability of the injured patient, especially those with fractures, to self-perform activities of daily living is severely affected due to restricted physical and functional roles. Subsequently, quality of life is affected negatively as well. Aim: To develop, implement and evaluate the impact of the “ADL self-management module” on the health related quality of life among Road traffic crashes patients with lower extremity fractures. Methods: The study design was a repeated measure quasi experiment with a control group. The study was conducted in Saudi Arabia, Taif City at two Ministry of Health hospitals. The study included patients who were admitted to the orthopedic units at the study hospitals with lower extremity fractures due to Road traffic crashes with difficulties in carrying out activities of daily living with a Barthel Index screening score ranging from 15 to 80. The patients in the intervention group were provided with an activity of daily living self-management intervention that was developed based on the individual and family self-management theory to improve quality of life. The control group received usual hospital care. The primary outcome was the quality of life measured using the EQ5D instrument. The secondary outcomes include patient activation for self-management and activity of daily living that were measured using PAM13 and Barthel Index instruments. The outcomes were measured at baseline, one month and four months post intervention. Data was analyzed using SPSS 23. Results: One hundred sixty patients agreed to participate with eighty patients in each group. The response rate was 91.5%. At four month follow up, seventeen and twenty two patients dropped out from the intervention and control group respectively. At baseline, the mean scores for quality of life were 51.03 ±11.71 for intervention and 48.965 ±13.66 for the control group while the activity of daily living were 30.08 ± 12.03 for intervention and 31.29 ±13.558 for the control group. Patient activation was 61.87± 13.307 for intervention and 59.90± 12.148 for the control group. Excluding the drop outs, there were no significant differences between the groups in participants’ characteristics and outcomes of interest at baseline (P˃0.05). In both measurements post intervention, health related quality of life as measured by EQ-VAS had improved significantly within and between intervention and control groups (P<0.001). On the other hand, EQ5D showed that pain/discomfort and depression/ anxiety domains did not differ significantly between groups. Activities of daily living and patient activation had improved significantly within and between groups as well (P<0.001). Conclusion: The intervention had a positive impact on research outcomes. Quality of life as the primary outcome had improved significantly within and between groups. This result was associated with an improvement in the secondary outcomes where patient activation and ability to perform activities of daily living independently had improved as well.